El proceso de selección de talentos en la etapa de iniciación deportiva en las escuelas de fútbol barriales de Liga Deportiva Universitaria de Loja, barrios Daniel Álvarez y Operadores, ciudad de Loja año 2015 - Garces Palacios, Hernan Aurelio (2016)
This research entitled: THE SELECTION OF TALENTS IN THE STAGE OF INITIATION SPORTS IN SCHOOLS FOOTBALL LEAGUE UNIVERSITY SPORTS BARRIALES Loja BARRIOS DANIEL ALVAREZ AND OPERATORS, Loja YEAR 2015 Cuyo problem arises What is the impact the talent selection process at the stage of sports initiation schools of neighborhood football LDU Loja? It had as its main objective: To generate a methodology for the selection of talent in the sport initiation phase of neighborhood schools football LDU Loja, neighborhoods and Operators Daniel Alvarez, Loja 2015 and specific objectives; Determine the talent selection process at the stage of sports initiation schools in the neighborhood of football LDU Loja, neighborhoods and Operators Daniel Alvarez. Designing the talent selection process at the stage of sport initiation in the neighborhood of schools football LDU Loja, neighborhoods Daniel Alvarez and Operators. Apply talent selection process at the stage of sports initiation schools of neighborhood football LDU Loja, Daniel Alvarez and Operators neighborhoods. evaluate the talent selection process at the stage of sports initiation schools in the neighborhood of football LDU Loja, neighborhoods and Operators Daniel Alvarez. As we review the literature category: Selecting talents, sport initiation, technical fundamentals of football. The methodology methods were used: scientific, descriptive and the results are structured in tables and graphs and analysis thereof which are the result of the application of techniques and instruments such as the observation guide athletes and surveys coaches. Coaches neighborhood schools football LDU (Loja) in the Operators and Daniel Alvarez neighborhoods do not develop any kind of selection and recruitment of sports talents specifically in the practice of football: results are obtained as. It is concluded that the selection of active and passive talents are crucial for the selection and recruitment of talent specifically in the practice of